Comparative Assessment of the Efficiencies of Activated Carbon from Banana Peels and Millet Husks in Waste Water Treatment. - Ntege, Abudu Swaburu (Kabale University, 2024)
This research presented the physical, chemical, and bacteriological parameters of wastewater at the Kigongi Treatment Plant, analyzing raw wastewater and two treatments using banana peels and millet husks. Key parameters include Temperature, Total Suspended Solids (TSS), Electrical Conductivity, Color, Turbidity, Total Alkalinity, and Total Dissolved Solids (TDS). Results show that the treatment significantly reduced TSS, color, and turbidity levels, with the Banana and Millet treatments yielding improved water quality compared to raw wastewater. This research investigates using banana peels and millet husks, abundant agricultural by-products, as sustainable alternatives for wastewater treatment. The project aims to address critical global challenges such as water pollution, high treatment costs, and the environmental risks associated with conventional methods. The removal efficiency of the Banana treatment for TSS was 23.33%, while Millet showed a 15.56% reduction. For color, Banana and Millet treatments achieved removal efficiencies of 29.33% and 20%, respectively. Turbidity reduction was observed at 15.72% for Banana and 7.55% for Millet. Other parameters such as Electrical Conductivity, TDS, and Total Alkalinity remained well within the national effluent discharge standards, with minimal variation between treatments. Bacteriological quality of wastewater treated using banana and millet media at the Kigongi Treatment Plant. Key parameters such as pH, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), E. coli, total phosphates, ammonia, and sulfates were analyzed. The results show that both treatment media improved the water quality, with banana treatment performing better for most parameters compared to millet.